The altered lipidome of hepatocellular carcinoma. (November 2022) - Tan, Shawn Lu Wen; Israeli, Erez; Ericksen, Russell E.; Chow, Pierce K.H.; Han, Weiping
Highlights: Lipidomics profiling and biochemical analyses of human HCCs reveal alterations in glycerophospholipid, sphingolipid, cholesterol and bile acid metabolism. Glycerophospholipid composition is commonly shifted towards increased MUFA-to-PUFA ratios in HCCs. Cholesterol esterification is augmented in HCCs. Loss of bile acid homeostasis occurs during hepatocarcinogenesis. Sphingolipid metabolism is often rewired to facilitate accumulation of sphingomyelins, sphingosine 1-phosphate and glycosphingolipids in HCCs. Abstract: Alterations in metabolic pathways are a hallmark of cancer. A deeper understanding of the contribution of different metabolites to carcinogenesis is thus vitally important to elucidate mechanisms of tumor initiation and progression to inform therapeutic strategies. Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death worldwide and its altered metabolic landscape is beginning to unfold with the advancement of technologies. In particular, characterization of the lipidome of human HCCs has accelerated, and together with biochemical analyses, are revealing recurrent patterns of alterations in glycerophospholipid, sphingolipid, cholesterol and bile acid metabolism. These widespread alterations encompass a myriad of lipid species with numerous roles affecting multiple hallmarks of cancer, including aberrant growth signaling, metastasis, evasion of cell death and immunosuppression. In this review, we summarize the current trends and findings of the altered lipidomic landscape of HCC and discuss their potential biological significance for hepatocarcinogenesis.